2010
DOI: 10.1177/1367493510380081
|View full text |Cite
|
Sign up to set email alerts
|

Do excessive internet use, television viewing and poor lifestyle habits affect low vision in school children?

Abstract: The aim of this study is to determine whether excessive internet use, television viewing and the ensuing poor lifestyle habits affect low vision in school children in a rapidly developing country. This is a cross-sectional study and 3000 school students aged between six and 18 years were approached and 2467 (82.2%) students participated. Of the studied school children 12.6 percent had low vision. Most of the low vision school children were in the 6-10 years age group and came from middle income backgrounds (41… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 19 publications
3
23
0
Order By: Relevance
“…However, they also spend less time than recommended on physical activities [39,40,41,42]. TV viewing is often accompanied with snacks or food and less outdoor activities, therefore tending to be related to lower vision and higher BMIs [43,44]. Our study showed that students with VI had lower levels of physical activity than children with normal vision, which was in line with other studies [40,41,45,46].…”
Section: Discussionsupporting
confidence: 89%
“…However, they also spend less time than recommended on physical activities [39,40,41,42]. TV viewing is often accompanied with snacks or food and less outdoor activities, therefore tending to be related to lower vision and higher BMIs [43,44]. Our study showed that students with VI had lower levels of physical activity than children with normal vision, which was in line with other studies [40,41,45,46].…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, this is the first study to investigate the relationship between internet addiction, fatigue and sleeping problems among young Turkish population. Bener et al 2011; Park et al 2013], physical inactivity [Bener et al 2010;Bener et al 2011;Kusss et al 2014;Griffiths 1996;Griffiths 1998] and adequate sleep [Canan et al 2013;Ekinci et al 2014;Bhandari et al 2017]. Furthermore, a Korean study reported a significant association between IA, sleep disturbances, fatigue symptoms, and fast food consumption [Kim et al 2010].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have documented adverse effects of IA among adolescents such as irregular dietary habits [Bener et al 2010;Bener et al 2011], physical inactivity, lack of adequate sleep [Choi et al 2009, Canan et al 2013, Ekinci et al 2014, increased depression, loneliness and social anxiety [Caplan 2007;Celik et al 2013]. These detrimental social and health effects are still being debated within the psychological, psychiatric and medical communities.…”
Section: Introductionmentioning
confidence: 99%
“…Amount of studies have been done focusing on addiction (Young, 2004), problematic use (Chen & Kim, 2013;Martinotti et al, 2011), or excessive use (Bener, Al-Mahdi, Vachhani, Al-Nufal, & Ali, 2010;Buckner, Castille, & Sheets, 2012) of the Internet and other technologies. Young (2004) has defined Internet addiction as an impulse-control disorder not involving an intoxicant, making it a 'behavioral addiction' akin to gambling addiction and unlike alcoholism.…”
Section: Introductionmentioning
confidence: 99%